Epithelial Cell-Neutrophil Interactions in the Alimentary Tract: A Complex Dialog in Mucosal Surveillance and Inflammation - Sean P. Colgan; Katrina M. Comerford; Donald W. Lawrence (The Scientific World Journal)
Inflammatory diseases of mucosal organs as diverse as the lung, kidney, and intestine, inevitably require the intimate interactions of neutrophils with columnar epithelia. The physiologic consequences of such interactions often determine endpoint organ function, and for this reason, much recent interest has developed in identifying mechanisms and novel targets for the treatment of mucosal inflammation. Elegant in vitro model systems incorporating purified human neutrophils and human epithelial cells grown in physiologic orientations have aided in discovery of new and insightful pathways to define basic inflammatory pathways. Here, we will review the recent literature regarding the interactions between columnar epithelial cells and neutrophils, with an emphasis on intestinal epithelial cells, structural aspects of neutrophil transepithelial migration, molecular determinants of neutrophil-epithelial cell interactions, as well as modulation of these pathways. These recent studies highlight the dynamic nature of these pathways and lend insight into the complexity of treating mucosal inflammation.